Thyroid Function in Normal Pregnancy - Rahman, M Hafizur; Chowdhury, Mahbub Ara; Moni, Sabiha Yasmin (KYAMC Journal, 2017)
Hormonal changes and metabolic demands during pregnancy result in alteration in the physiological and biochemical parameters of thyroid function. Among the many physiological alterations which may occur during pregnancy are thyroid enlargement, increased thyroid capability for iodine uptake and increase in serum thyroxine and tri-iodothyronine concentration. However these findings are not usually associated with symptoms of hyperthyroidism. To clarify the changes, a study was undertaken in Rajshahi Medical College Hospital when serum specimens were collected from individual woman at different stages of normal pregnancy and women married but non pregnant. Among the study subjects, 22 women were in their 1st trimester, 20 women were in their 2nd trimester, 32 women were in their 3rd trimester of normal pregnancy and 10 women were married but non pregnant. We have measured serum levels of total and free thyroxine (TT4 & FT4) and total and free triiodothyronine (TT3 & FT3 ) by using RIA. During the 1st trimester of pregnancy serum FT4 and FT3 concentrations are significantly higher than in non pregnant women and women in 3rd trimester. The concentration of FT4 and FT3 progressively declined as the pregnancy advanced and are to control level in the 3rd trimester. The mean serum TT4 and TT3 are significantly elevated throughout pregnancy in comparison to control. KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 415-418